2016
DOI: 10.1021/acs.chemmater.5b04964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Tunable Curcumin Incorporated Polyurethane Hydrogels as Potential Biomaterials

Abstract: We report here on the one-pot synthesis and characterization of curcumin incorporated polyethylene glycol−polyurethane (PU-CUR) hydrogels using PEG-4000, 4, 4′methylenebis (cyclohexyl isocyanate), curcumin in the presence of a cross-linker, 1,2,6 hexanetriol (HT). Besides the physical entrapment, curcumin also provides a partial crosslinking in the 3-D structure of the hydrogel. The degree of swelling in hydrogels could be controlled by varying the amount of HT as well as curcumin. The structural characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…In the synthesis, there is the advantage of liquid triol which is difficult to crystallize. Another research group has reported the synthesis of polyurethane hydrogels using 1,2,6‐hexanetriol as a liquid triol . In the ratio of crosslinker, PU‐Gly0.05 was not a completely formed gel because of the limitation of reactivity in the applied condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the synthesis, there is the advantage of liquid triol which is difficult to crystallize. Another research group has reported the synthesis of polyurethane hydrogels using 1,2,6‐hexanetriol as a liquid triol . In the ratio of crosslinker, PU‐Gly0.05 was not a completely formed gel because of the limitation of reactivity in the applied condition.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, polyurethane hydrogels have attracted attention as a polymer design to overcome such challenges due to their biodegradability and excellent mechanical properties . Polyurethane hydrogels are designed and synthesized with diisocyanates, and crosslinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Water (pH 5.8), acid (pH 1.2) and a basic phosphate buffered saline solution (pH 7.4) were used as aqueous medium and, at a predetermined time, the mass of swollen samples was precisely weighed on an electronic analytical balance. The water uptake ratio was calculated using the equation given in reference which relates the weight of the swollen and dried sample. The experiment was conducted with three independent samples; the results are presented as the data average.…”
Section: Methodsmentioning
confidence: 99%
“…The literature reports that hydrophobic curcumin could be used as a multi‐therapeutic agent, displaying a variety of biological and pharmacological properties such as anti‐inflammatory, antioxidant, antimicrobial, anticarcinogenic and schistosomal activities . Divakaran et al . produced hydrogels based on polyethylene glycol−polyurethane containing curcumin (PU‐CUR) as potential biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al used 3,3 -disulfanediyldipropane-1,2-diol (DSO) as the second crosslinker for preparation of DC PEG-PU hydrogels, the highest value of tensile strength among these hydrogels was 0.25 MPa [33]. Divakaran et al also prepared a DC PEG-PU hydrogel with the tensile strength of 0.7 MPa and the breaking elongation of 284% at equilibrium swelling state, in which 1,2,6-hexanetriol and curcumin were used as crosslinkers [34]. These studies suggest that the DC PEG-PU hydrogels are able to be fabricated by using the polyhydroxy compound as the second crosslinking agent and the mechanical strength of obtained PEG-PU hydrogels is higher than the single crosslinked PEG-PU hydrogels, but their strength, stretchability and toughness need to be further improved.…”
Section: Introductionmentioning
confidence: 99%